Posted by **Anonymous** on Friday, March 15, 2013 at 4:56pm.

Suppose G={x E N : x> 1} and H ={-3;-2; -1; 0; 1; 2}

which statement is true?

G=[1;

## Answer this Question

## Related Questions

- math - Which of the following conclusions is true about the statement below? x^2...
- Mth 209 - Which of the following conclusions is true about the statement below? ...
- geometry - State what conclusion can be made IFx=5 and the given statement is ...
- Algebra II - In an induction proof of the statement 4+7+10+...+(3n-1)=n(3n+5)/2 ...
- math - can someone correct this for me... solve: -4(2x - 3) = -8x + 5 my answer...
- Math Quadratic Equations - 1. Which of the following conclusions is true about ...
- math - 1)Find the third iterate x3 of f(x)=x2-4 for an initial value of x0=2 A)-...
- MATH I NEED HELP PLEASE - 1. Which of the following conclusions is true about ...
- geometry - Rafael wrote the statements shown in the chart. Statement 1 ...
- physics - Consider the following statement: “When a rifle is fired horizontally...